Interaction between ACE insertion/deletion polymorphism and type 2 diabetes mellitus in pancreatic cancer risk: Evidence from an Algerian cohort - Hamiouda, Imene; Laouar, Rania; Salhi, Choubeila; Khenchoul, Youcef; Sifi, Karima; Satta, Dalila (Archives of Biological Sciences, 2026)
Paper description: Specific genetic variations in the angiotensin-converting enzyme gene and type 2 diabetes (T2D) have both been independently studied for their links to pancreatic cancer, with inconsistent results across different populations. We conducted a genetic case-control study in Algeria, comparing 35pancreatic cancer patients to 140 healthy controls to analyze this gene-diabetes interaction. We discovered that the risk from gene variation was significantly elevated only in individuals with T2D, revealing a critical interaction. This identifies a high-risk patient subgroup for potential targeted screening and suggests that existing blood pressure drugs targeting this system warrant investigation for pancreatic cancer prevention. Abstract: Pancreatic cancer risk was investigated in relation to the angiotensin-I-converting enzyme (ACE) insertion/deletion (I/D) polymorphism and its interaction with type 2 diabetes mellitus in an Eastern Algerian population through a hospital-based case-control study. The research involved 35 patients with confirmed pancreatic cancer and 140 matched healthy controls. Genotyping was performed to determine ACE I/D profiles, and statistical analysis was used to quantify risk associations. Type 2 diabetes mellitus was common, affecting more than half of the patients. The heterozygous ID genotype was associated with a 2.5-fold increased cancer risk, and this association was significant only among individuals with diabetes. Multivariable analysis suggested the ID genotype as an independent risk factor, with an approximately 8-fold higher risk after adjustments. This preliminary study suggests the ACE I/D polymorphism may influence pancreatic cancer risk, with type 2 diabetes acting as a critical effect modifier and identifying a potential high-risk subgroup for targeted surveillance. These exploratory findings warrant validation in larger, population-based cohorts.